2018
DOI: 10.18632/oncotarget.25170
|View full text |Cite
|
Sign up to set email alerts
|

Administration of bifidobacterium and lactobacillus strains modulates experimental myasthenia gravis and experimental encephalomyelitis in Lewis rats

Abstract: Probiotics beneficial effects on the host are associated with regulation of the intestinal microbial homeostasis and with modulation of inflammatory immune responses in the gut and in periphery. In this study, we investigated the clinical efficacy of two lactobacillus and two bifidobacterium probiotic strains in experimental autoimmune myasthenia gravis (EAMG) and experimental autoimmune encephalomyelitis (EAE) models, induced in Lewis rats. Treatment with probiotics led to less severe disease manifestation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 86 publications
4
59
0
Order By: Relevance
“…We observed that the therapeutic treatment with BBmix was associated with increased FoxP3 and TGFβ mRNAs expression in drLNs of EAMG animals (Figure 2A). This observation is in line with our previous report on the efficacy of preventive probiotic treatment in this model (6); overall, these data further support the hypothesis of TGFβ as systemic cytokine able to orchestrate the immune-modulation activated by probiotics (6), besides FoxP3 + cells as key players in probiotic induced-suppressive activity (43,44).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that the therapeutic treatment with BBmix was associated with increased FoxP3 and TGFβ mRNAs expression in drLNs of EAMG animals (Figure 2A). This observation is in line with our previous report on the efficacy of preventive probiotic treatment in this model (6); overall, these data further support the hypothesis of TGFβ as systemic cytokine able to orchestrate the immune-modulation activated by probiotics (6), besides FoxP3 + cells as key players in probiotic induced-suppressive activity (43,44).…”
Section: Discussionsupporting
confidence: 92%
“…Over the past years, many studies have been conducted and demonstrated the benefits of probiotic treatment in animal models of inflammatory diseases, such as experimental arthritis (3), experimentally induced colitis (4) and experimental autoimmune encephalomyelitis (5). Effects of probiotic administration on clinical symptoms and on immune mechanisms of EAMG has been investigated by us and other groups, according to a preventive or prophylactic/preventive protocol (6,7). We previously demonstrated the effects of the preventive administration of two bifidobacteria strains or two lactobacilli strains in the Lewis rats EAMG model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, the family Lachnospiraceae has been previously associated with butyrate production and has also been correlated with IL-10 and TGF-β production by different immune cells [65]. Regarding Bifidobacteria, probiotics composed of different strains including Bifidobacterium have exhibited beneficial effects in EAE [11,69] and MS [17,18] and have been correlated with anti-inflammatory immune markers. Concerning Vivomixx, composed by genera Lactobacillus, Bifidobacterium, and Streptococcus, the observed increase in the genus Streptococcus (family Streptococcaceae) is consistent with probiotic composition, with prior studies in Vivomixx-treated MS patients, and connected to anti-inflammatory responses affecting mainly DCs and monocytes [17,18].…”
Section: Discussionmentioning
confidence: 85%
“…One of the safe and appropriate ways to modulate T cells in MS is to orally administer specific autoantigens [13,14]. Administration of Bifidobacteria or Lactobacteria probiotic strains to mice has been shown to increase Treg cells and tumor growth factor (TGF)-β levels and reduce the severity of EAE clinical symptoms, in parallel with improvement in the regeneration of myelin in the spinal cord compared to the control [15,16]. Administration of both Bifidobacteria and Lactobacteria strains induce an additional significant delay in the onset of EAE and related clinical symptoms, together with a substantial reduction of mononuclear infiltration into the CNS, and increased level of Treg cells of the CD4 + CD25 + Foxp3 + phenotype in mouse spleen and lymph nodes.…”
Section: Introductionmentioning
confidence: 99%